Possibility of Using Concrete Reinforced by Carbon Fibre in Construction - Mahdi Fawzi Aljalawi, Nada; M.K. Al-Jelawy, Haider (International Journal of Engineering and Technology, 2018)
This work focuses on studying the mechanical characteristics of carbon fibre reinforced concrete, containing a different percentage of fibre. This work was carried out using several tests. These tests were hardened density, compressive strength, flexural strength . Tests were performed for specimens at ages of (7,28,60) days. The test results indicated that the inclusion of fibre in the reference concrete mixes did not affect the compressive strength significantly, while the flexural strength was improved. Test results indicated that the flexural strength of (0.75%) carbon fibre concrete specimens are twice that of the reference specimens in age of 28 days . The percentage of increasing the flexural strength for carbon mixes containing fibre by volume fraction of (0.5%, 0.75%) were (23%, 27%) respectively at age of 28 days.Â